Novel therapies of treating non-muscle invasive bladder cancer when BCG therapy turns out to be insufficient - Kołodziej, Magdalena; Kozicz, Michał Andrzej; Saiuk, Nazarii; Marcicka, Justyna; Mądry, Wojciech; Mazurkiewicz, Aleksandra; Męczyńska, Joanna; Seredyński, Tomasz; Wojciechowska, Adriana; Salasa, Weronika (Journal of Education, Health and Sport, 2024)
Introduction: Bladder cancer is one of the most common cancers in the world. There are two forms of bladder cancer: non-muscle invasive bladder cancer and muscle invasive bladder cancer. A common treatment method for non- muscle invasive bladder cancer is intravesical BCG (Mycobaterium bovis) therapy after radical tumor resection. It is estimated that half of patients will have an insufficient response to BCG treatment. Patients using this type of therapy also report side effects more and more often. Aim of the study: The aim of this article is to discuss the latest discoveries in the treatment of non-muscle invasive bladder cancer when BCG therapy is insufficient. Material and Methods: The paper was created based on the PubMed and Scholar database. The literature was reviewed using the key words: „bladder cancer”; „BCG”; „treatment”; „side effects”; „novel therapies”. Results: The research shows that novel therapies are effective and safe compared to the use of BCG. In such patients, atezolizumab, metformin or intravesical magnesium sulfate infusions may be used as an alternative. An innovative solution is the use of HIVEC - heated chemotherapy administered intravesically. There are also drugs that potentiate the action of BCG, making the therapy more effective. These include: sasanlimab and rapamycin. Due to the side effects experienced by patients, the use of intravesical BCG is often replaced with intravesical infusions of chemotherapy drugs. Conclusion: The research shows that novel therapies are effective compared to the use of BCG. Unfortunately, more research is needed to standardize the treatment of non-muscle invasive bladder cancer.